Soara the stinging spectre - Blade, Adam (Blade, Adam. Beast quest series 18, 2016)
Tom and Elenna have tackled many Beast Quests before, but now there is a challenger for his title of Master of the Beasts! Join them as they fight a new set of Beasts and battle to save the kingdom...